Four-week induction of type 2 diabetes mellitus in rats by streptozotocin and high-fat diet - Bowonsomsarit, Wirin; Anegkamol, Weerapat; Chuaypen, Natthaya; Kaewwongse, Maroot; Tosukhowong, Piyaratana; Prapunwattana, Phisit; Dissayabutra, Thasinas (Chulalongkorn Medical Journal, 2021)
Background: Current rodent models for diabetes mellitus type 2 could be divided into genetic-engineered and environmental-induced. Since genetic-modified rodents are difficult to acquire and costly for Thai researchers, we tried to develop a protocol for food-induced diabetic rats. Objectives: To develop a convenient and economical type 2 diabetic mellitus rats with a short course (4 - week) of induction for research purpose. Methods: Eight-week-old male Wistar rats were divided into two groups: control group and streptozotocin with high-fat diet (STZ-HFD) group (n = 4 each). The control group received normal chow (c.p.082 diet with 20.0% energy from fat). For the STZ-HFD group, STZ (30 mg/kg) was intraperitoneal injected at week 0 of experiment with HFD feeding (58.0% energy from fat). Rats were fed ad libitum. Blood samples were collected for diabetic evaluation weekly for 4 weeks. Results: The body weight of the STZ-HFD group was significantly higher than that of the control group. Blood glucose, plasma insulin, homeostasis model assessment of insulin resistance (HOMA-IR) index and HbA1C were increased in the STZ-HFD group. Moreover, STZ-HFD rats suffered with a non-alcoholic fatty liver disease. Conclusion: Low dose STZ injection (30 mg/kg) with HFD feeding (58.0% energy from fat) could be used to induced type 2 diabetes in rats within 4 weeks.